PENGARUH GREEN REWARD FINANSIAL DAN KOMITMEN ORGANISASI TERHADAP GREEN PERFORMANCE MANAGEMENT - Junaidi, Muhammad; Kasmi, Kasmi; Martiah, Anisa; Kesuma, Aghesna Rahmatika (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to analyze the influence of Green Financial Rewards and Organizational Commitment on Green Performance Management, both partially and simultaneously. The background of this study is based on the importance of implementing Green Human Resource Management (GHRM) as a company strategy in improving sustainability, efficiency, and environmentally friendly performance. The study was conducted at PT Jasa Marga Tbk Lampung using a quantitative approach through a survey method. The research sample consisted of 133 respondents who were employees, selected using a purposive sampling technique. The research instrument was a questionnaire consisting of 6 items for Green Financial Rewards, 9 items for Organizational Commitment, and 7 items for Green Performance Management, with a five-point Likert scale. Data analysis used multiple linear regression through SPSS, after going through validity, reliability, and classical assumption tests. The results of the study indicate that Green Financial Rewards have a positive and significant effect on Green Performance Management (t = 3.494; Sig. 0.001). Organizational Commitment also has a positive and significant effect (t = 4.839; Sig. 0.000). Simultaneously, both variables have a significant effect (F = 86.751; Sig. 0.000) with a coefficient of determination (R²) of 0.536. This means that 53.6% of the variation in Green Performance Management is explained by the two independent variables, while 46.4% is influenced by other factors outside the model. This finding confirms the importance of implementing GHRM in supporting the company's sustainable performance.